1968
DOI: 10.2118/2129-pa
|View full text |Cite
|
Sign up to set email alerts
|

How To Flood a Tight Sand

Abstract: The Moore-Holverson-Hill-Aagard waterflood is followed from 1963 start-up to Jan., 1968. The Bartlesville sand body is marginal by normal waterflooding standards, but secondary oil recovery to date and production trends point to an ultimate recovery that will be twice the point to an ultimate recovery that will be twice the average for other "successful" floods in the county. Water quality, wettability and treatment with polymer are documented. Special emphasis is placed on the amount of extra oil produced fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The clay-stabilization process has been successfully demonstrated in several clay-sensitive reservoirs (Nugent et al 1975;Sloat and Larsen 1984;Sydansk 1984). The polymeraugmented imbibition process has been used both with and without clay stabilization as a secondary recovery technique in some midwestern and western reservoirs with considerable success (Sloat and Brown 1968;Haines 1985;Hochanadel and Townsend 1990). To date, no literature has been found that indicates that this process has rejuvenated an essentially abandoned field that has undergone extensive waterflooding.…”
Section: Process Descriptionmentioning
confidence: 99%
“…The clay-stabilization process has been successfully demonstrated in several clay-sensitive reservoirs (Nugent et al 1975;Sloat and Larsen 1984;Sydansk 1984). The polymeraugmented imbibition process has been used both with and without clay stabilization as a secondary recovery technique in some midwestern and western reservoirs with considerable success (Sloat and Brown 1968;Haines 1985;Hochanadel and Townsend 1990). To date, no literature has been found that indicates that this process has rejuvenated an essentially abandoned field that has undergone extensive waterflooding.…”
Section: Process Descriptionmentioning
confidence: 99%